Handbook of Nondestructive Evaluation, 3E - Hellier, Chuck (McGraw-Hill Education, 2020)
This up-to-date resource covers the latest methods for examining materials without destroying them or altering their structure. The book offers comprehensive details on the background, benefits, limitations, and applications of each technique. You will discover how to perform effective tests, interpret results, and formulate accurate decisions based on your findings. Ideal both as a textbook and as a study guide to prepare for certification examinations, the book clearly discusses visual, ultrasonic, radiography, and thermal infrared testing-and much more.